Guided Inquiry Learning with Experimental Methods During the Pandemic Period in Improving Physics Learning Outcomes of High School Students - Hadi, Sofyan; Izzati, Nurul; Aulia, Rizka Nurul Atmi; Rahmat, Solihin; Trisnawati, Trisnawati; Dinda, Yayi Ana (AMPLITUDO : Journal of Science and Technology Innovation, 2022)
This writing aims to provide readers with views on the application of the inquiry learning model with the experimental method during the Covid-19 pandemic. During the pandemic, the government decided to implement online learning which was still less effective in improving student learning outcomes, especially in Physics lessons. Physics lessons are factual lessons, and tend to be calculation activities so that a learning model is needed that allows students to be able to think critically and systematically. This writing uses a literature study by reviewing several articles in national journals. From various journal sources